Endocan and a novel score for dyslipidemia, oxidative stress and inflammation (DOI score) are independently correlated with glycated hemoglobin (HbA(1c)) in patients with prediabetes and type 2 diabetes - Klisic, Aleksandra (Arch Med Sci, 2019)
INTRODUCTION: We aimed to examine serum endocan level and the summary involvement of dyslipidemia, oxidative stress (OS) and inflammation by calculation of its comprehensive score (i.e. Dyslipidemia-Oxy-Inflammation (DOI) score) in relation to glucoregulation in subjects with prediabetes and overt type 2 diabetes (T2D). MATERIAL AND METHODS: A total of 59 patients with prediabetes and 102 patients with T2D were compared with 117 diabetes-free controls. Glycated hemoglobin (HbA(1c)), inflammation, OS and lipid parameters were measured. Associations of clinical data with HbA(1c) level were tested with univariate and multivariate logistic ordinal regression analysis. HbA(1c) as a dependent variable is given at the ordinal level (i.e. < 5.7%; 5.7–6.4%, > 6.4%, respectively). RESULTS: Endocan was significantly higher in the T2D group than in the controls. As endocan concentration rose by 1 unit, the probability for higher HbA(1c) concentration increased by more than 3 times (OR = 3.69, 95% CI: 1.84–7.01, p < 0.001). Also, a rise in the dyslipidemia score, oxy score, inflammation score and DOI score by 1 unit increased the probability of higher HbA(1c) concentration by 19%, 13%, 51% and 11%, respectively. In the models, after adjustment for confounding variables, endocan and DOI score remained independent predictors of HbA(1c) level. CONCLUSIONS: Endocan and DOI score are independently correlated with HbA(1c) in patients with prediabetes and overt T2D.